Influence of subsidence after stand-alone anterior cervical discectomy and fusion in patients with degenerative cervical disease: A long-term follow-up study. Issue 38 (23rd September 2022) - Ryu, Han-Seung; Han, Moon-Soo; Lee, Shin-Seok; Moon, Bong Ju; Lee, Jung-Kil
Abstract : This study aimed to evaluate the influence of subsidence in patients who performed stand-alone anterior cervical discectomy and fusion (ACDF) by analyzing the long-term clinical and radiological outcomes. This retrospective study enrolled 53 patients with 79 segments with degenerative cervical disease treated with stand-alone ACDF with ≥5 years of follow-up. Segmental angle (SA), cervical sagittal alignment (CSA), subsidence, and fusion were analyzed. Visual analog scale (VAS) scores and neck disability index (NDI) were also evaluated. Subsidence occurred in 24 (45.2%) patients and 38 segments (48.1%) at the last follow-up. The mean VAS score and NDI had improved in both the subsidence and non- subsidence groups. The mean SA at the last follow-up had increased to 1.3° ± 8.5° in the subsidence group and to 1.5° ± 5.2° in the non-subsidence group compared with the post-operative SA ( P  < .001). The overall mean CSA at the last follow-up increased over time in both the groups compared with the post-operative CSA ( P  = .003). The fusion rate at 1 year after surgery was 86.8% and 82.9% in the subsidence and non-subsidence groups, respectively. However, the differences in the SA, CSA, and fusion rates between the groups were not statistically significant ( P  = .117, .98, and .682, respectively). Subsidence after stand-alone ACDF occurs to a certain capacity; however, it does not appear to significantly influence the radiological and clinical outcomes if foramen decompression is adequately and sufficiently provided in a long-term follow-up study. In contrast, subsidence appears to positively affect the fusion rate in the short-term follow-up.